Experimental data for thermal conductivity and dielectric properties of wood and wood-based materials - Noreen Saeed (Data in Brief, 2022)
Empirical data and methods of measurements for the research article “Experimental correlation of thermal conductivity with dielectric properties of wood and wood-based construction materials: Possibilities for rapid in-situ building energy evaluation” by Saeed et al. [1] is presented. The data offers an insight into the possible correlation between thermal conductivity and dielectric properties of wood and wood-based materials. There is independent data on thermal conductivity and dielectric properties of wood in the literature. However, data correlating the two properties is scarce, making our dataset unique. Data on the dielectric properties, thermal conductivity, density, and moisture content of 30 solid wood and 17 wood-based materials is presented. Wood-based materials include plywood, OSB, chipboard, and MDF. Measurements were made on 50 mm x 25 mm samples, typically 25 mm thick. The thermal conductivity was measured using the steady state method with a heat flow meter apparatus. Dielectric properties were measured using an unshielded system of two electrodes with an LCR meter at 10 kHz and 100 kHz frequencies at room temperature. All measurements were made in the transverse direction for solid woods and perpendicular to the face of the boards for wood-based materials.